Study on the Performance of Superlattice-Like Thin Film V2O5/Sb in Phase Change Memory. (27th February 2020) - Xu, Yongkang; Hu, Yifeng; Sun, Song; Zhu, Xiaoqin; Lai, Tianshu; Song, Sannian; Song, Zhitang
Abstract : Compared with Sb film, V2 O5 /Sb superlattice-like thin film has better thermal stability ( T c ∼ 240 °C, T 10-year ∼ 172.9 °C). V2 O5 /Sb thin film is suppressed by the multiple interfaces and the grains become smaller. The vibrational peaks of Sb-Sb and V–O bonds are observed by Raman measurement. The interaction between the two crystal systems improves the stability of the V2 O5 /Sb membrane. The multilayer structures before and after crystallization were observed by transmission electron microscopy. The ultralow-power (2.25 × 10 −12 J) and ultrafast-speed (8 ns) has been achieved for V2 O5 (1 nm)/Sb(9 nm)-based phase change memory device.